Gene coexpression analysis reveals key pathways and hub genes related to late-acting self-incompatibility in Camellia oleifera - Li, Chang; Long, Yi; Lu, Mengqi; Zhou, Junqin; Wang, Sen; Xu, Yan; Tan, Xiaofeng (Frontiers in Plant Science, 2023)
Self-incompatibility (SI) is an important strategy for plants to maintain abundant variations to enhance their adaptability to the environment. Camellia oleifera is one of the most important woody oil plants and is widely cultivated in China. The property of late-acting self-incompatibility (LSI) in C. oleifera results in a relatively poor fruit yield in the natural state, and understanding of the LSI mechanism remains limited. To better understand the molecular expression and gene coexpression network in the LSI reaction in C. oleifera, we conducted self- and cross-pollination experiments at two different flower bud developmental stages (3–4 d before flowering and 1 d before flowering), and cytological observation, fruit setting rate investigation and RNA-Seq analysis were performed to investigate the mechanism of the male‒female interaction and identify hub genes responsible for the LSI in C. oleifera. Based on the 21 ovary transcriptomes, a total of 7669 DEGs were identified after filtering out low-expression genes. Weighted gene coexpression network analysis (WGCNA) divided the DEGs into 15 modules. Blue and pink were identified as the crucial modules anchoring LSI reaction genes. KEGG analysis indicated that flavonoid biosynthesis, plant MAPK signaling pathways, ubiquitin-mediated proteolysis, and plant-pathogen interaction were the crucial pathways for the LSI reaction. Fifty-four important transcription factors (TFs) were obtained in the two key modules, and WRKY and MYB might play an important role in LSI in C. oleifera. Network establishment indicated that genes encoding G-type lectin S-receptor-like serine (lecRLK), isoflavone 3'-hydroxylase-like (CYP81Q32), cytochrome P450 87A3-like (CYP87A3), and probable calcium-binding protein (CML41) were the hub genes that positively responded to the LSI reaction. The other DEGs inside the two modules, including protein RALF-like 10 (RALF), F-box and pectin acetylesterase (MTERF5), might also play vital roles in the LSI reaction in C. oleifera. Overall, our study provides a meaningful resource for gene network studies of the LSI reaction process and for subsequent analyses of pollen‒pistil interactions and TF roles in the LSI reaction, and it also provides new insights for exploring the mechanisms of the LSI response.